Factors involved in the stability of isolated β-sheets: Turn sequence, β-sheet twisting, and hydrophobic surface burial - Santiveri, Clara M. (Cold Spring Harbor Laboratory Press, 2004)
We have recently reported on the design of a 20-residue peptide able to form a significant population of a three-stranded up-and-down antiparallel β-sheet in aqueous solution. To improve our β-sheet model in terms of the folded population, we have modified the sequences of the two 2-residue turns by introducing the segment DPro-Gly, a sequence shown to lead to more rigid type II′ β-turns. The analysis of several NMR parameters, NOE data, as well as Δδ(CαH), ΔδC(β), and Δδ(Cβ) values, demonstrates that the new peptide forms a β-sheet structure in aqueous solution more stable than the original one, whereas the substitution of the DPro residues by LPro leads to a random coil peptide. This agrees with previous results on β-hairpin-forming peptides showing the essential role of the turn sequence for β-hairpin folding. The well-defined β-sheet motif calculated for the new designed peptide (pair-wise RMSD for backbone atoms is 0.5 ± 0.1 Å) displays a high degree of twist. This twist likely contributes to stability, as a more hydrophobic surface is buried in the twisted β-sheet than in a flatter one. The twist observed in the up-and-down antiparallel β-sheet motifs of most proteins is less pronounced than in our designed peptide, except for the WW domains. The additional hydrophobic surface burial provided by β-sheet twisting relative to a “flat” β-sheet is probably more important for structure stability in peptides and small proteins like the WW domains than in larger proteins for which there exists a significant contribution to stability arising from their extensive hydrophobic cores.